2011
DOI: 10.1177/2040622310389227
|View full text |Cite
|
Sign up to set email alerts
|

Pitavastatin: finding its place in therapy

Abstract: Dyslipidaemia is a major risk factor for cardiovascular (CV) disease. Despite the widespread availability of effective lipid-lowering agents, an unacceptably large proportion of patients fail to attain their target low-density lipoprotein cholesterol (LDL-C) level in clinical practice. Reasons for this include undertreatment, poor adherence/persistence with therapy and failure to address non-LDL-C residual risk factors such as high levels of triglycerides, low high-density lipoprotein cholesterol (HDL-C) conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 111 publications
0
3
1
Order By: Relevance
“…To sum up, pitavastatin seems to act via a dual mechanism increasing HDL numbers, thus inhibiting HDL catabolism and stimulating HDL synthesis. However, these results contradict other studies that indicate a decrease in cholesterol efflux mediated by ABCA1 after statin treatment [ 50 ]. Nonetheless, a meta-analysis of statin treatment demonstrated a substantial decrease in mortality and CV events, including stroke and myocardial infarction, in more than 18,000 individuals with type 2 diabetes mellitus.…”
Section: Hdl In Pathologycontrasting
confidence: 99%
“…To sum up, pitavastatin seems to act via a dual mechanism increasing HDL numbers, thus inhibiting HDL catabolism and stimulating HDL synthesis. However, these results contradict other studies that indicate a decrease in cholesterol efflux mediated by ABCA1 after statin treatment [ 50 ]. Nonetheless, a meta-analysis of statin treatment demonstrated a substantial decrease in mortality and CV events, including stroke and myocardial infarction, in more than 18,000 individuals with type 2 diabetes mellitus.…”
Section: Hdl In Pathologycontrasting
confidence: 99%
“…Clinically, simvastatin lactone formation seems less relevant, because it is administered as the lactone form, already resulting in relatively high plasma lactone levels. , The observed patterns of steady-state lactonization with atorvastatin, cerivastatin, and pitavastatin are similar to previous findings, except for the absence of cerivastatin lactone formation by UGT1A1. Here, we found that the extensive lactonization of pitavastatin by UGT2B7 was not observed with any of the other statins. An explanation for this remarkable difference could be the unique cyclopropyl moiety of pitavastatin, which not only increased the inhibitory potency against HMC-CoA-reductase but also resulted in diversion from CYP3A4 metabolism. Another study indicated that this group possibly also influenced the bioavailability and hepatocellular uptake by the organic anion transporting polypeptide (OATP)­1B1 . Furthermore, replacement of the cyclopropyl moiety by an isopropyl side chain significantly decreased its HMG-CoA reductase inhibitory potency. , Future studies are needed to indicate whether such a replacement of the cyclopropyl moiety also decreases the pitavastatin lactonization by UGT2B7.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with gradual stenosis elevation in all 4 angiograms developed anginal symptoms, while those without changes had uncomplicated courses (Shin et al, 2015). Despite similar baseline nonobstructive disease and treatment, fast plaque development significantly increased the chance of plaque rupture and MI (Ose, 2011).…”
Section: Plaque Rupturementioning
confidence: 99%